Functional changes in Tezno, the industrial zone in Maribor - Lorber, Lučka (Journal for Geography, 2006)
The article discusses the impact of the initial establishment of TAM (Tovarna avtomobilov in motorjev Maribor) on forming of the industrial zone Tezno, Maribor. Both industrialization and planning economy played a key role in forming of a classic industrial zone, which represented an area of manufacturing activities. In the 1970s and 1980s, Maribor economy made more than a half of total income in secondary sector. Under the influence of socioeconomic changes, restructuring economies and its adaptation to the requirements of the common European market in 1990s influenced on functionaly changes of the industrial zone and on forming of the new business and production zone. The city acceded to the revitalisation of the industrial zone into a perspective Business and production zone Tezno.
Keywords: industrialization; industrial zone; restructuring economies; TAM; Maribor; business and production zone; Tezno